Understanding Effective Use of Big Data: Challenges and Capabilities (A Management Perspective) - Surbakti, Feliks Prasepta Sejahtera (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
While prior research has provided insights into challenges and capabilities related to effective Big Data use, much of this contribution has been conceptual in nature. The aim of this study is to explore such challenges and capabilities through an empirical approach. Accordingly, this paper reports on a multiple case study approach, involving eight organizations from the private and public sectors. The study provides empirical support for capabilities and challenges identified through prior research and identifies additional insights viz. problem-driven approach, time to value, data readiness, data literacy, data misuse, operational agility, and organizational maturity assessment.